2019
DOI: 10.12928/telkomnika.v17i3.12212
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare receivers’ acceptance of telecardiology in Malaysia

Abstract: This quantitative study investigates acceptance towards implementation of telecardiology inMalaysia. The purpose of this study is to explore and understand the potential factors that could be the key elements in cultivating positive behaviour towards telecardiology adoption in Malaysia. Data was gathered by using survey method from 149 patients and publics who use internet service in their daily lives. The questionnaire was developed by integrating Technology Readiness Index (TRI), Technology Acceptance Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Positive views act as motivators, contributing positively to TR, whilst negative views conceive the inhibitors that diminish consumers' TR. The views were categorized in four dimensions: optimism and innovativeness as TR motivators, and discomfort and insecurity as TR inhibitors (Yeo et al, 2019). These dimensions reflect relative distinct behaviors that can lead, in some cases, even to paradoxical consolidated results, such as concomitant strong positive and negative feelings toward a technology by the same consumer (Parasuraman & Colby, 2015).…”
Section: Technology Readinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive views act as motivators, contributing positively to TR, whilst negative views conceive the inhibitors that diminish consumers' TR. The views were categorized in four dimensions: optimism and innovativeness as TR motivators, and discomfort and insecurity as TR inhibitors (Yeo et al, 2019). These dimensions reflect relative distinct behaviors that can lead, in some cases, even to paradoxical consolidated results, such as concomitant strong positive and negative feelings toward a technology by the same consumer (Parasuraman & Colby, 2015).…”
Section: Technology Readinessmentioning
confidence: 99%
“…Moreover, telehealth -i.e., the use of ICT in health servicesbecomes more relevant when patients experience reduced mobility, such as the need for social distancing during the COVID-19 pandemic (Smith et al, 2020). Many studies have already shown telehealth's significant potential to enhance healthcare practices (Yeo, Al-Ashwal, Handayani, & Lee, 2019), particularly during the COVID-19 pandemic (Scott & Mars, 2020). Despite the importance of ICT in consumers' health-related services, it is still necessary to improve the understanding of its acceptance and diffusion, identifying relevant factors that can influence the acceptance of innovative technologies in health services (Kayser et al, 2018).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…In assessing the acceptance of online health care, Jung (2008) reported that no impact by perceived ease of use was found on any mediating or dependent construct (Jung, 2008). Users' intention to adopt new technology is mainly by influenced perceived ease of use and perceived usefulness; medical personnel are more likely Predicting e-PHR acceptance to use and benefit from monitoring patients' health condition, thereby enhancing efficiency or work performance (Yeo et al, 2019).…”
Section: Structural Model Resultsmentioning
confidence: 99%
“…Past research in information systems has extensively used the technology acceptance model (TAM). Yeo et al (2019) found that TAM showed a significant level of perceived usefulness and perceived ease of use toward health-care technology implementation in Malaysia. Yuan and Cheah (2020) applied TAM to study the acceptance of IoT application in health-care sector among Malaysian users.…”
mentioning
confidence: 95%
“…Prior to the formal distribution of the questionnaire, the items of different constructs were tested to ensure that they were clearly described and could be easily understood by the respondents. Exploratory factor analysis (EFA) and reliability test were subsequently conducted to remove any items having low reliability and non-validity (Yeo, Al-Ashwal, Handayani & Lee, 2019). A Cronbach's alpha score above .75 generally represents a scale of high reliability, while a score of .5 to .75 is considered to be of a moderately reliable scale (Hinton, McMurray & Brownlow, 2014).…”
Section: B Research Instrumentmentioning
confidence: 99%